PTB and TIAR binding to insulin mRNA 3′- and 5′UTRs; implications for insulin biosynthesis and messenger stability. Issue 9 (September 2016) - Fred, Rikard G.; Mehrabi, Syrina; Adams, Christopher M.; Welsh, Nils
Abstract: Objectives: Insulin expression is highly controlled on the posttranscriptional level. The RNA binding proteins (RBPs) responsible for this result are still largely unknown. Methods and results: To identify RBPs that bind to insulin mRNA we performed mass spectrometry analysis on proteins that bound synthetic oligonucloetides mimicing the 5′- and the 3′-untranslated regions (UTRs) of rat and human insulin mRNA in vitro . We observed that the RBPs heterogeneous nuclear ribonucleoprotein (hnRNP) U, polypyrimidine tract binding protein (PTB), hnRNP L and T-cell restricted intracellular antigen 1-related protein (TIA-1-related protein; TIAR) bind to insulin mRNA sequences, and that the in vitro binding affinity of these RBPs changed when INS-1 cells were exposed to glucose, 3-isobutyl-1-methylxanthine (IBMX) or nitric oxide. High glucose exposure resulted in a modest increase in PTB and TIAR binding to an insulin mRNA sequence. The inducer of nitrosative stress DETAnonoate increased markedly hnRNP U and TIAR mRNA binding. An increased PTB to TIAR binding ratio in vitro correlated with higher insulin mRNA levels and insulin biosynthesis rates in INS-1 cells. To further investigate the importance of RNA-binding proteins for insulin mRNA stability, we decreased INS-1 and EndoC-βH1 cell levels of PTB and TIAR by RNAi. In both cell lines, decreased levels of PTB resulted in lowered insulin mRNA levels while decreased levels of TIAR resulted in increased insulin mRNA levels. Thapsigargin-induced stress granule formation was associated with a redistribution of TIAR from the cytosol to stress granules. Conclusions: These experiments indicate that alterations in insulin mRNA stability and translation correlate with differential RBP binding. We propose that the balance between PTB on one hand and TIAR on the other participates in the control of insulin mRNA stability and utilization for insulin biosynthesis.